Factors influence graduates' repayment behaviour towards education loan, PTPTN in Klang Valley / Sharifah Fatin Aishah Jamalolai Syed Ikmal Hashim - Syed Ikmal Hashim, Sharifah Fatin Aishah Jamalolai (2017)
Starting last year, 2016, National Higher Education Fund Corporation (PTPTN) has stopped giving full loans to students pursuing studies at a higher level. This is due to the continuous trend of poor rate of repayment by graduates. This research is conducted to investigate the factors that influence graduates' repayment behavior towards education loan, PTPTN. The factors influence are independent variables for this paper which are perceptions that loan repayment affected the quality of life after graduation, attitude towards education loan, and belief towards loan agreement. The graduates' repayment behavior is the dependent variable. The population consists of local graduates who were Malaysian from a public and private universities/college staying or working in Klang Valley. This study is a descriptive study using questionnaire based on 100 participants. The types of investigation are correlation relationship. The study setting is non-contrived with minimal researcher interference. The time horizon for this study is cross-sectional and the unit analysis is individuals. This paper expects to know the significant factors that influence graduates' repayment behavior towards education loan, PTPTN. The expected findings were all independent variables (perceptions that loan repayment affected the quality of life after graduation, attitude towards education loan, and belief towards loan agreement) has a relationship with the dependent variables, graduates' repayment behavior.